The effectiveness of stress management implementation on work motivation and turnover intention and its implications on employee performance - Sugandi Mastia Anugrah; Sri Rochani Mulyani; Widjadjanti Utoyo (Jurnal Scientia, 2024)
This study aims to analyze the effectiveness of stress management implementation on work motivation and turnover intention and its impact on employee performance at Sogaten Hospital, Madiun City. The population consists of 421 employees with a sample of 80 people selected using the Slovin formula. Data were collected through questionnaires that have been tested for validity and reliability. The analysis was conducted using path analysis, correlation coefficient, and coefficient of determination. The results of the analysis show that stress management has a significant effect on work motivation (p < 0.05; R2 = 0.233) and turnover intention (p < 0.05; R2 = 0.268). Work motivation also has a significant effect on performance (p < 0.05; R2 = 0.521), while turnover intention has a significant negative effect on performance (p < 0.05; R2 = 0.058). However, simultaneously, work motivation and turnover intention have no significant effect on performance (p > 0.05; R2 = 0.059). In addition, stress management has a direct influence on employee performance (path coefficient = 0.268). However, the indirect effect through work motivation (path coefficient = 0.07) and turnover intention (path coefficient = -0.124) is not statistically significant. This study provides an understanding of the importance of stress management in increasing work motivation and reducing turnover intention, which in turn can affect employee performance at RSUD Sogaten Madiun City.